MicroRNA Expression and Intestinal Permeability in Children Living in a Slum Area of Bangladesh - Rashid, Humaira; Siddiqua, Towfida J.; Hossain, Biplob; Siddique, Abdullah; Kabir, Mamun; Noor, Zannatun; Alam, Masud; Ahmed, Mamun; Haque, Rashidul (Frontiers in Molecular Biosciences, 2021)
Introduction: MicroRNAs (miRNAs) are small, non-coding RNAs that post-transcriptionally regulate gene expression. Changes in miRNA expression have been reported in a number of intestinal diseases, in both tissue samples and readily accessible specimens like stools. Pathogenic infections, diet, toxins and other environmental factors are believed to influence miRNA expression. However, modulation of miRNAs in humans is yet to be thoroughly investigated. In this study, we examined the expression levels of two human miRNAs (miRNA-122 and miRNA-21) in stool samples of a group of Bangladeshi children who had an altered /increased intestinal permeability (IIP). Method: Stool samples were collected from children with IIP (L:M >.09) and normal intestinal permeability (NIP) (L:M ≤.09). Quantitative PCR was performed to quantify the levels of miRNA-122 and miR-21 in stools. Commercial ELISA kits were used to measure gut inflammatory markers Calprotectin and REG1B. Serum samples were tested using Human Bio-Plex Pro Assays to quantify IL-1β, IL-2, IL-5, IL-10, IL-13, IFN-γ and TNF-α. Total nucleic acid extracted from stool specimens were used to determine gut pathogens using TaqMan Array Card (TAC) system real-time polymerase chain reaction. Results: The expression levels of miRNA-122 (fold change 11.6; P<0.001, 95% CI: 6.14-11.01) and miR-21 (fold change 10; P<0.001, 95% CI:5.05-10.78) in stool were upregulated in children with IIP than in children with normal intestinal permeability (NIP). Significant correlations were observed between stool levels of miR-122 and miR-21 and the inflammatory cytokines IL-1β, IL-2, IFN-γ and TNF-α (P<0.05). Children with IIP were frequently infected with rotavirus, Campylobacter jejuni, Bacteroides fragilis, adenovirus, norovirus, astrovirus and various Escherichia coli strains (ETEC_STh, ETEC_STp, EAEC_aaiC, EAEC_aatA) (P<0.001). miR-122 significantly correlated with the fecal inflammatory biomarkers REG1B (P=0.015) and Calprotectin (P=0.030), however miR-21 did not show any correlation with these fecal biomarkers. Conclusions: miR-122 and miR-21 may be associated with intestinal permeability. Assessment of these miRNAs may provide new tools for diagnosis of IIP in children from developing countries suffering diseases associated with intestinal barrier dysfunction.